Co-management approach to sustainable management of marine protected areas: The case of Malaysia. (April 2022) - Masud, Muhammad Mehedi; Shahabudin, Sharifah Muhairah; Baskaran, Angathevar; Akhtar, Rulia
Abstract: The management of Marine Protected Areas (MPAs) and sustainable use of natural and marine resources require the collective participation of the government and host community. This study aims to uncover the community's perception of co-management approach and its perceived impact on the development of diverse resources of MPAs in Malaysia. A survey questionnaire was used to collect data, which was then analysed using partial least square structural equation modelling (PLS-SEM). The findings revealed that most of the participants acknowledged the co-management approach as necessary to conserve and develop the diverse natural resources. They believed it will increase cooperation, collaboration and coordination among various associated parties, and encourage social interaction among the community members. The findings also indicated that community financial resources have improved marginally, including job prospects, business opportunities, access to business financing and other financial benefits for marine park residents. Furthermore, the adoption of co-management approach is considered essential for the development of financial, natural and physical resources. In other words, the community maintains that implementing a co-management structure will boost the development of diverse resources and promote the sustainable management of physical resources. Therefore, policymakers and concerned authorities should consider the implementation of co-management approach to ensure the sustainable use of natural resources and socioeconomic development of the marine park residents.